Pengaruh Transparansi Keuangan Desa terhadap Pengelolaan Bantuan Langsung Tunai Dana Desa di Kabupaten Aceh Barat - Lismawati, Lismawati; Marlina, Lilis; Rahmadani, Ika; Fatmayanti, Fatmayanti (Regress: Journal of Economics & Management, 2025)
Economic inequality in income distribution and regional disparities underscores the importance of sustaining Village Fund programs, particularly Direct Cash Assistance financed through Village Funds, to reduce social imbalances. Nevertheless, the implementation of this assistance has encountered governance challenges, including alleged fund deductions in Rundeng Village, Johan Pahlawan Subdistrict, West Aceh Regency. This study examines whether village financial transparency significantly influences the management effectiveness of Direct Cash Assistance funded by Village Funds in West Aceh Regency. Employing a quantitative approach with purposive sampling, the research was conducted in 21 villages within Johan Pahlawan Subdistrict and involved 105 respondents consisting of village officials and assistance beneficiaries, with hypotheses tested using simple linear regression analysis. The findings reveal that village financial transparency has a positive and statistically significant effect on the effectiveness of assistance management, with a regression coefficient of 0.465; however, the coefficient of determination (R Square) of 17.6 percent indicates that other structural and administrative factors also contribute substantially. These results affirm that strengthening transparency mechanisms constitutes a critical prerequisite for improving accountability and governance quality in village-level social assistance programs.